A Law for regulating and establishing the Militia in the Territory of the United States north-west of the river Ohio, Chapter I(B)(4), in Laws Passed in the Territory of the United States North-West of the River Ohio from the Commencement of the Government to the 31 of December, 1791 (printed by Francis Childs and John Swaine), page 30, 31 - (:unkn) unknown (General Publisher, 1788)
Required all males aged sixteen and upwards to be equipped and accoutred with a musket, bayonet, rifle, cartridge box and pouch, powder horn and bullet pouch, with forty rounds of cartridges, or one pound of powder and four pounds of lead, priming wire, and brush with six flints.
--
Keywords: REQUIRED POSSESSION